2015
DOI: 10.1177/0363546515580790
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Overuse Injuries in Collegiate and High School Athletics in the United States

Abstract: Overuse injuries can impose a significant burden on college and high school athletes. Interventions addressing prevention of overuse injury are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
156
3
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(174 citation statements)
references
References 34 publications
(45 reference statements)
10
156
3
5
Order By: Relevance
“…For concussion in the NCAA ISP, this value was expressed as concussion injuries per 10 000 AEs. Previous authors have reported IRs per 10 000 AEs, 10,11 which are easier to interpret than 1000 AEs (ie, 7.85/10 000 AEs versus 0.785/1000 AEs).…”
Section: Injury Ratementioning
confidence: 89%
“…For concussion in the NCAA ISP, this value was expressed as concussion injuries per 10 000 AEs. Previous authors have reported IRs per 10 000 AEs, 10,11 which are easier to interpret than 1000 AEs (ie, 7.85/10 000 AEs versus 0.785/1000 AEs).…”
Section: Injury Ratementioning
confidence: 89%
“…According to some reports, overuse injuries account for 46% to 50% of all athletic injuries. [8][9][10] In high school athletes alone, overuse injuries represented 7.7% of all injuries. 11 Actual injury rates vary by age, sex, and sport.…”
Section: Epidemiology and Backgroundmentioning
confidence: 99%
“…The men's severe injury rate was higher in ice hockey and lacrosse, whereas the women's rate was higher in basketball, cross-country, soccer, and track and field. Past researchers looking at the high school level noted higher rates in girls than in boys, particularly in soccer, 12 but sports such as ice hockey and lacrosse were not examined. In these sports, checking is allowed by the males but not by the females.…”
Section: Sex Differencesmentioning
confidence: 99%
“…6 Much of the current literature focuses on the adolescent population 6 or pertains to particular sports, injury mechanisms, or diagnoses. [12][13][14][15] Because the literature on severe injuries in collegiate student-athletes is limited, we used data from the NCAA Injury Surveillance Program (NCAA ISP) to describe the epidemiology of severe injury in 25 NCAA sports.…”
mentioning
confidence: 99%